ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) PADA PT. INDO FOOD SUKSES MAKMUR.TBK - Rudy Chairudin; Kartawinata Kartawinata (Fakultas Ekonomi Universitas Tridinanti Palembang, 2021)
The purpose of this study is find out the company's financial performance as well as information material for the public in investing in a company. As one of the measurements of financial performance is Economic Value Added (EVA) where this tool is used to measure the results of the company's financial performance as well as to find out whether the results of management or corporate financial decisions so far can increase or decrease the company's finances. From the results of this study it can be concluded that PT. Indo Food Sukkses Makmur Indonesia has a satisfactory financial performance, especially in 2017 and 2019 which has a positive EVA value, while for 2018 it has a negative EVA value due to an increase in cost of goods sold and financial costs in the use of short-term debt